Hubungan Implementasi Biaya Pendidikan Gratis dengan Minat Belajar Siswa - Wolio, Asis; Saidah, Ummu; Rajab, La (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2021)
One of the efforts to implement improvements in the field of education is to implement the school policy of Providing cheap and easy education for the people which means that education must be organized for the people which must be easy to follow or reach for all people. This study aims to determine the relationship between the implementation of free education costs and students' interest in learning. Subject 6 students 1 teacher. Data were collected through observation, interviews, and documentation. This research uses research types in the form of data grouping, data reduction, and data interpretation. The results of this study found that the implementation of free education fees is very helpful for students in learning when at school or at home. With free tuition fees students can concentrate in studying and diligently to go to school. In addition, students' interest in learning is very good, this can be seen in the learning process and students' enthusiasm to know and understand well the material presented by the teacher in class.